Determination of Thermomechanical Stresses in Elements of Vehicles’ Braking Systems - Oleksii Grevtsev; Ninel Selivanova; Pavlo Popovych; Liubomyr Poberezhny; Yurii Rudyak; Oksana Shevchuk; Liubov Poberezhna; Olena Skyba; Viktor Ostroverkhov; Oleksandr Shashkevych (Communications - Scientific letters of the University of Zilina, 2022)
The main objective of the study was to develop a model and analyze the thermomechanical behavior of the hub material of the vehicle brake disk. The simulation strategy was based on the solution of the three-dimensional problem of the theory of elasticity for the case of effect of external loads and temperature fields on the metal structure element of the vehicle brakes. To solve this type of task of the theory of elasticity, the differential equations of the second order were used for the first time. Adaptation of the proposed model, completed in the article, has proved the correctness of use of these equations in modeling the thermomechanical processes with determination of stresses and displacements in unevenly heated rotary cylinders of the final length. The proposed method can be applied with high efficiency in stress strain state simulation of individual parts of vehicles.